Case Report: Unilateral optic perineuritis as the initial presentation of multiple myeloma - Jung, Eugene; Choi, Jae-Hwan; Choi, Kwang-Dong; Choi, Seo-Young (Frontiers in Ophthalmology, 2025)
BackgroundMultiple myeloma (MM) is typically diagnosed based on systemic symptoms such as anemia or fatigue, or through imaging findings of bone lytic lesions. Neurologic manifestations as the initial presentation are rare. In this case, we report a patient diagnosed with MM after presenting with severe, unilateral vision loss.MethodsA 67-year-old woman presented with a 5-day history of painless vision loss in her left eye. Her visual acuity was severely reduced to light perception, yet both the optic disc and retinal vessels appeared normal upon examination. Blood tests revealed no significant abnormalities except for anemia. Magnetic resonance imaging (MRI) revealed enhancement of the left optic nerve sheath, and bone marrow biopsy confirmed MM. High-dose steroid and subsequent chemotherapy led to significant visual improvement.ConclusionsUnilateral optic perineuritis can be the first manifestation of MM, potentially caused by immune-mediated mechanisms or direct tumor cell infiltration near the optic nerve. Steroid not only contributed to symptom improvement but also may have played a role in partial remission of MM.